Dimensi Teks Berita Online Larangan Mudik 2021 di Tempo.com dan Kompas.com dalam Perspektif Teun A. Van Dijk - Kusumawati, Hesty; Yasin, Roychan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2021)
In its role, the media is the conveyor of information through discourses that will influence the perception of the masses. The presentation of a news cannot be separated from the ideology of the media and media journalists. The choice of words used by journalists in a text shows how one's meaning of facts or reality is based on ideology. Critical discourse analysis is always interesting to study more deeply. Discourse by Van Dijk is described as having three dimensions or structures: text, social cognition, and social context. This study aims to describe the analysis of Van Dijk discourse in the text dimension of the news on the prohibition of going home in the media Tempo.com and Kompas.com. The approach used in this research is descriptive qualitative with note-taking techniques and Teun A. Van Dijk's discourse analysis techniques. The results showed three structures of the news text. The macro structure shows differences in global coherence, the first news is about the negative impact of policies while the second news is policy considerations. The superstructure consists of summaries and stories based on selected perspectives from global coherence. While in the micro structure there are semantic, syntactic, stylistic and rhetorical studies, the four studies also display the meaning of the background, details, intentions, presuppositions, and sentence building that supports the perspective of each news.